STUDIES ON THE ANTIBIOTIC SENSITIVITY PATTERN OF ISOLATES OF P. MULTOCIDA FROM BUFFALOES - M. Kamran; M. U. D. Ahmad; A. A. Anjum; A. Maqbool; K. Muhammad; M. Nawaz; N.U. Hudda; S. Sana; M. A. Ali (Journal of Animal and Plant Sciences, 2014)
Antibiotic susceptibility patternof Pasteurella multocida causing hemorrhagic septicemia in buffaloes was determined. The Pasteurella multocida (n=11) were isolated from healthy (04) and diseased buffaloes (07) of four districts of Sargodha division. Isolates were identified by cultural, biochemical and serological characteristics, and confirmed by specie specific polymerase chain reaction. All isolates were subjected to antibiotic susceptibility testing against gentamicin, erythromycin, amoxicillin, ampicillin, chloramphenicol, ciprofloxacin, norfloxacin, enrofloxacin, sulfadiazine and amikacin by disc diffusion method. Results revealed that P. multocida were highly sensitive to enrofloxacin (90.91 %) followed by gentamicin, chloramphenicol, ciprofloxacin and norfloxacin (72.73%). Susceptibility of P. multocida isolates was low against ampicillin and amoxicillin (45.45%), amikacin (36.36%), sulfadiazine (18.18%) and erythromycin (18.18%). It was concluded that quinolones (enrofloxacin, ciprofloxacin and norfloxacin) are better choice for the treatment of hemorrhagic septicemia as the level of resistance in P. multocida against the macrolides, sulfa drugs and beta lactams has increased enormously.
Keywords: Hemorrhagic septicemia; Pasteurella multocida; Buffalo; Antibiotic susceptibility; Quinolones